A Vibrating Mesh Nebulizer as an Alternative to the Collison Three-Jet Nebulizer for Infectious Disease Aerobiology - Bowling, Jennifer D. (Appl Environ Microbiol, 2019)
Experimental infection of animals with aerosols containing pathogenic agents is essential for an understanding of the natural history and pathogenesis of infectious disease as well as evaluation of potential treatments. We evaluated whether the Aeroneb nebulizer, a vibrating mesh nebulizer, would serve as an alternative to the Collison nebulizer, the “gold standard” for generating infectious bioaerosols. While the Collison possesses desirable properties that have contributed to its longevity in infectious disease aerobiology, concerns have lingered about the liquid volume and concentration of the infectious agent required to cause disease and the damage that jet nebulization causes to the agent. Fluorescein salt was added to the nebulizer contents to assess pathogen loss during aerosolization. Relative to fluorescein salt, loss of influenza virus during aerosolization was worse with the Collison than with the Aeroneb. Four other viruses also had superior aerosol performance with the Aeroneb. The Aeroneb did not improve the aerosol performance for a vegetative bacterium, Francisella tularensis. Environmental parameters collected during the aerosol challenges indicated that the Aeroneb generated a higher relative humidity in exposure chambers while not affecting other environmental parameters. The aerosol mass median aerodynamic diameter (MMAD) was generally larger and more disperse for aerosols generated by the Aeroneb than what is seen with the Collison, but ≥80% of particles were within the range that would reach the lower respiratory tract and alveolar regions. The improved aerosol performance and generated particle size range suggest that for viral pathogens, the Aeroneb is a suitable alternative to the Collison three-jet nebulizer for use in experimental infection of animals. IMPORTANCE Respiratory infection by pathogens via aerosol remains a major concern for both natural disease transmission as well as intentional release of biological weapons. Critical to understanding the disease course and pathogenesis of inhaled pathogens are studies in animal models conducted under tightly controlled experimental settings, including the inhaled dose. The route of administration, particle size, and dose can affect disease progression and outcome. Damage to or loss of pathogens during aerosolization could increase the dose required to cause disease and could stimulate innate immune responses, altering outcome. Aerosol generators that reduce pathogen loss would be ideal. This study compares two aerosol generators to determine which is superior for animal studies. Aerosol research methods and equipment need to be well characterized to optimize the development of animal models for respiratory pathogens, including bioterrorism agents. This information will be critical for pivotal efficacy studies in animals to evaluate potential vaccines or treatments against these agents.